Effect of Clean and Healthy Life Behavior on Diarrhea Disease - Auliailahi, Annisa Rizki; Oginawati, Katharina (Research of Environmental Science and Engineering, 2020)
Clean and healthy life behavior (CHLF) towards diarrheal disease is a community health improvement program that can be applied in various environments. Diarrhea is a disease with a high incidence among people living in urban areas with high density. This study aims to determine the relationship between the application of the CHLF principle with the number of diarrheal diseases in the Cicadas area. This study uses a questionnaire method relating to Clean and Healthy Life Behavior with the incidence of diarrheal diseases and sampling of raw water quality used by the community with the Total Coliform microbiological parameters. The results of this study indicate that the application of aspects of the availability of clean water, the use of healthy latrines and the application of the habit of washing hands with soap and clean running water have a direct relationship with the incidence of diarrheal diseases in the scope of households in Cicadas area. In addition, the results of laboratory water quality tests with indicators of the presence of Coliform bacteria showed that 27 of the 30 water samples taken proved to be positive containing Coliform bacteria, and all were positive for Escherichia coli bacteria.